Comparison of the impact of melatonin on chronic ethanol-induced learning and memory impairment between young and aged rats - Baydas, G; Yasar, A; Tuzcu, M (Wiley, 2005)
Chronic alcohol exposure causes functional and structural changes in nervous system which have all been associated with learning and memory impairments. Furthermore, alcohol consumption has been shown to alter the pattern of neural cell adhesion molecules (NCAM) which are involved in memory processes. In the current work, we investigated the effects of melatonin on learning and memory deficits induced by alcohol exposure in young and aged rats. A group of young rats (3 months old) were administered ethanol for 45 days and half of them were co-treated with melatonin. Similar treatments were performed in the aged (19 months old) rats. Morris water maze test and passive avoidance task were used to assess cognitive performance. Lipid peroxidation (LPO) and glutathione (GSH) levels were determined to characterize the level of oxidative stress in the hippocampus and cortex. NCAM levels were determined by Western blotting in the hippocampal homogenates. There was a significant elevation in LPO levels and a reduction in GSH levels in aged and alcohol-exposed rats. Furthermore, both young and aged rats displayed some cognitive impairment when given with alcohol for 45 days. Co-administration of melatonin with ethanol significantly reduced LPO and elevated GSH levels while improving the learning and memory deficits induced by ethanol; the aged rats exhibited a greater response to melatonin supplementation. Moreover, melatonin modulated NCAM expression in hippocampus. Present findings indicate that exposure to ethanol induces learning and memory deficits probably by generating reactive oxygen species and downregulating NCAM 180 in hippocampus of aged rats. Melatonin improves learning and memory deficits and the behavioral responses of rats to melatonin supplementation are age dependent.
Keywords: glutathione; learning; lipid peroxidation; melatonin; neural cell adhesion molecules